Sigma-1 Receptors in Depression: Mechanism and Therapeutic Development - Ren, Peng; Wang, Jingya; Li, Nanxi; Li, Guangxiang; Ma, Hui; Zhao, Yongqi; Li, Yunfeng (Frontiers in Pharmacology, 2022)
Depression is the most common type of neuropsychiatric illness and has increasingly become a major cause of disability. Unfortunately, the recent global pandemic of COVID-19 has dramatically increased the incidence of depression and has significantly increased the burden of mental health care worldwide. Since full remission of the clinical symptoms of depression has not been achieved with current treatments, there is a constant need to discover new compounds that meet the major clinical needs. Recently, the roles of sigma receptors, especially the sigma-1 receptor subtype, have attracted increasing attention as potential new targets and target-specific drugs due to their translocation property that produces a broad spectrum of biological functions. Even clinical first-line antidepressants with or without affinity for sigma-1 receptors have different pharmacological profiles. Thus, the regulatory role of sigma-1 receptors might be useful in treating these central nervous system (CNS) diseases. In addition, long-term mental stress disrupts the homeostasis in the CNS. In this review, we discuss the topical literature concerning sigma-1 receptor antidepressant mechanism of action in the regulation of intracellular proteostasis, calcium homeostasis and especially the dynamic Excitatory/Inhibitory (E/I) balance in the brain. Furthermore, based on these discoveries, we discuss sigma-1 receptor ligands with respect to their promise as targets for fast-onset action drugs in treating depression.